2013
DOI: 10.1007/s00208-013-0961-y
|View full text |Cite
|
Sign up to set email alerts
|

A sub-Riemannian curvature-dimension inequality, volume doubling property and the Poincaré inequality

Abstract: Let M be a smooth connected manifold endowed with a smooth measure µ and a smooth locally subelliptic diffusion operator L satisfying L1 = 0, and which is symmetric with respect to µ. We show that if L satisfies, with a non negative curvature parameter, the generalized curvature inequality introduced by the first and third named authors in [BG1], then the following properties hold:• The volume doubling property; • The Poincaré inequality;• The parabolic Harnack inequality.The key ingredient is the study of dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(120 citation statements)
references
References 30 publications
2
118
0
Order By: Relevance
“…A remarkable aspect of (3.1) is that it is equivalent to the lower bound Ricci ≥ ρ on the Ricci tensor of M. In the paper [15] it was shown that many global properties of the heat semigroup, in a setting which includes the Riemannian one, can be derived exclusively from a generalization of the curvature-dimension inequality (3.1). In this connection one should also see [14], [11] and [12].…”
Section: A Curvature-dimension Inequalitymentioning
confidence: 92%
“…A remarkable aspect of (3.1) is that it is equivalent to the lower bound Ricci ≥ ρ on the Ricci tensor of M. In the paper [15] it was shown that many global properties of the heat semigroup, in a setting which includes the Riemannian one, can be derived exclusively from a generalization of the curvature-dimension inequality (3.1). In this connection one should also see [14], [11] and [12].…”
Section: A Curvature-dimension Inequalitymentioning
confidence: 92%
“…Recall that the doubling volume property and two-sided bounds for the heat kernel p(x, y, t) has been established by Baudoin et al, see Theorem 3.8 (or Theorem 3.1) and Theorem 4.1 respectively in [8]: for every ε > 0, there exist constants C 1 = C 1 (ρ 2 , k, d) > 0, C 2 (ε) = C 2 (ε, ρ 2 , k, d) > 0 such that for every x, y ∈ M and t > 0,…”
Section: Gradient Estimate For the Heat Kernelsmentioning
confidence: 96%
“…Under the generalized curvature-dimension inequality CD(ρ 1 , ρ 2 , k, d) introduced in [9], we first establish the Hamilton type gradient estimate for positive and upper bounded solutions to heat equations, see Theorem 2.1. Combining with the doubling volume property and the lower (upper) bounds for the heat kernel established by Baudoin et al [8], we can get the gradient estimate for the associated heat kernel, see Theorem 3.1.…”
Section: Introduction and Frameworkmentioning
confidence: 94%
“…Preliminaries. In this section we study the setting similar to [5]. We state relevant details here for completeness.…”
Section: Sub-riemannian Manifoldsmentioning
confidence: 99%